Hybrid layer quality of universal adhesives: a systematic literature review (Research, Society and Development, 2023)
Currently, the availability of a wide variety of universal adhesives makes it difficult for clinicians to choose the correct system for different bonding situations to the dentin substrate. This work presents a systematic review that evaluated the quality of the hybrid layer created by different application strategies of universal adhesive systems, in both self-etching and etching-and-rinsing modes, with the aim of investigating whether the differences observed in the hybrid layer are significant for clinical practice. Two reviewers conducted a bibliographic search until December 2022 in the PubMed (MedLine) electronic database. Only in vitro studies that evaluated the quality of the hybrid layer using confocal laser scanning microscopy and that reported the effect of using universal adhesives on the quality of the dentin hybrid layer were included. It was found that the application mode of universal adhesives influences the quality of the hybrid layer. Adhesives applied in etching-and-rinsing mode present a thicker hybrid layer with greater extensions in dentinal tubules. However, self-etching adhesives demonstrate greater longevity due to their resin-dentin interface being more resistant to aging and studies show that an etching approach prior to adhesive system application does not improve bond strength. Based on these results, we can conclude that the self-etching approach is the most advantageous option for application in dentin, as it provides greater longevity and less possibility of nanoleakage and degradation of the hybrid layer with aging.